2017
DOI: 10.1016/j.apenergy.2016.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic assessment of solar assisted heat pump system retrofit in the Canadian housing stock

Abstract: The techno-economic feasibility of retrofitting existing Canadian houses with solar assisted heat pump (SAHP) is investigated. The SAHP architecture is adopted from previous studies conducted for the Canadian climate. The system utilizes two thermal storage tanks to store excess solar energy 10 for use later in the day. The control strategy is defined in order to prioritise the use of solar energy 11 for space and domestic hot water heating purposes. Due to economic and technical constraints a 12 series of eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A large number of publications was made within the IEA task 44 on solar and heat pump systems in 2010 to 2013 [17]. Asaee et al [18] studied by simulation the performance of a SAHP system and made an economic feasibility analyses of retrofitting houses in Canada with the system. They found that the system could reduce the energy consumption of the houses.…”
Section: Solar Assisted Heat Pump Systems -Experimental Studiesmentioning
confidence: 99%
“…A large number of publications was made within the IEA task 44 on solar and heat pump systems in 2010 to 2013 [17]. Asaee et al [18] studied by simulation the performance of a SAHP system and made an economic feasibility analyses of retrofitting houses in Canada with the system. They found that the system could reduce the energy consumption of the houses.…”
Section: Solar Assisted Heat Pump Systems -Experimental Studiesmentioning
confidence: 99%
“…Heat pumps have generally been found to reduce energy consumption and emissions. In Canadian studies, air-to-water heat pumps reduced the greenhouse gas emissions of the housing stock by 23% [22], while solar-assisted Energies 2019, 12, 4395 3 of 29 heat pumps reduced emissions by 19% [23]. Here, the key question is how the electricity to run the heat pumps is produced, as larger reductions are achievable with low emission electricity.Bjørneboe et al [24] confirmed through a year-long monitoring campaign that simulated energy savings of a renovated single-family house matched those of a real building.…”
mentioning
confidence: 99%
“…Summary of identified impact factors. ,17,20,24,27,32,36,40,41,43,46,49,51,57,[59][60][61][62]69,75,76,78,80,83,85,86,88,89,92,93,95,97,98,108,111,115,117,121,124,130,137,148,150,153,155,161,167,184,186,193,200,204,207,…”
mentioning
confidence: 99%